1998
DOI: 10.1016/s1078-5884(98)80055-5
|View full text |Cite
|
Sign up to set email alerts
|

Duplex scanning and effect of multisegmental arterial disease on its accuracy in lower limb arteries

Abstract: Duplex is an accurate tool in diagnosis of lower limb arterial disease and multisegmental pathology does not adversely effect this accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 16 publications
0
7
0
3
Order By: Relevance
“…Other studies have reported that multisegment disease has no effect on DUS accuracy in the diagnosis of LE arterial disease. 25,26 In one study, Sacks et al 27 reported that accuracy of DUS in detecting stenosis was reduced in the presence of adjacent disease if absolute PSV values are used. However, if Vr was used to classify the degree of stenosis, then adjacent disease did not affect the accuracy of DUS.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported that multisegment disease has no effect on DUS accuracy in the diagnosis of LE arterial disease. 25,26 In one study, Sacks et al 27 reported that accuracy of DUS in detecting stenosis was reduced in the presence of adjacent disease if absolute PSV values are used. However, if Vr was used to classify the degree of stenosis, then adjacent disease did not affect the accuracy of DUS.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Sensier et al 28 concluded that PSVR ≥ 2 was efficient to detect isolated lesions (even if the sensitivity was low: Se = 65%, Sp = 96%) as well as adjacent lesions (Se = 88%, Sp = 86%). Indeed, Aly et al 5 proved that PSVR > 2 was less sensitive in the presence of isolated lesions when compared to multiple stenoses.…”
Section: Discussionmentioning
confidence: 99%
“…Os achados angiográficos foram quantificados através da medida acurada das estenoses, nos clichês radiográficos. As dúvidas em relação a algumas 8,[25][26][27][28][29][30][31][32][33][34][35][36][37] . No presente trabalho, a acurácia para se distinguir uma lesão hemodinamicamente significativa de outra não-significativa foi de 92%.…”
Section: Protocolo Da Madunclassified
“…Essa conclusão está de acordo com quase todos os trabalhos da literatura 8,[25][26][27][28][29][30][31][32][33][34][35][36][37][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] . A eco-Doppler pode ser usada na investigação primária da DOAI, evitando-se a angiografia pré-intervenção por qualquer método (arteriografia com cateter, tomografia computadorizada e ressonância magnética) na imensa maioria dos pacientes com suspeita de DOAI.…”
Section: Conclusãounclassified